Pervasive translation of small open reading frames in plant long non-coding RNAs - Sruthi, K. Bharathan; Menon, Athira; P, Akash; Vasudevan Soniya, Eppurath (Frontiers in Plant Science, 2022)
Long non-coding RNAs (lncRNAs) are primarily recognized as non-coding transcripts longer than 200 nucleotides with low coding potential translationally inactive transcripts with a length>200 nucleotides and are present in both eukaryotes and prokaryotes. However, recent findings reveal discoveries have indicated that lncRNAs can code for micro-peptides in various species of plants and animals. Micropeptides are generated from small open reading frames (smORFs) and have been discovered frequently in short mRNAs and non-coding RNAs, such as lncRNAs, circular RNAs, and pri-Such peptide-encoding lncRNAs have small ORFs (open reading frames), which can code for small functional peptides.miRNAs. The most accepted definition of a smORF is an ORF containing fewer than 100 codons, and ribosome profiling and mass spectrometry are the most prevalent experimental techniques used to identify them miRNA precursors and circular have also been shown to encode peptides in plants. Although the majority of micropeptides perform critical roles throughout plant developmental processes and stress conditions, only a handful of their functions have been verified to dateThe functions of all identified peptides have not been verified yet, although most of them play crucial roles during developmental processes and stress conditions in plants. Even though more research is being directed toward identifying micropeptides, there is still a dearth of information regarding these peptides in plants. This review outlines the lncRNA-encoded peptides, the evolutionary roles of such peptides in plants, the techniques used to identify them in plants, and the methods used to identify them. It also describes the functions of the talks about specific pri-miRNA and circRNA-encoded peptides that have been identified in plants. and their functions. Keywords:non-coding RNA.N.A.s, long non-coding RNA.N.A. (lncRNA), micropeptide, small ORF (smORF),miPEPs), miPEP.